Pengaruh Penggunaan Situs Web Bijakdemokrasi.Id Terhadap Peningkatan Literasi Politik Generasi Muda : Studi Korelasional terhadap Pengguna Situs Web bijakmemilih.framer.website - Nabila Ayu Lestari; Qotrun Nida (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to determine the effect of the use of the BijakDemokrasi.Id Website (bijakmemilih.framer.website) on increasing political literacy of the Young Generation and to be able to find out the Implementation of the Movement that has been carried out by the Bijak Memilih Team in increasing Political Literacy of the Young Generation. The Use of the BijakDemokrasi.Id Website (bijakmemilih.framer.website) is used to be able to increase Political Literacy of the Young Generation towards a healthier Indonesian Democratic Climate. This study uses Quantitative Methodology with a Correlational design. The population of this study were active Users and Visitors to the BijakDemokrasi.Id Website (bijakmemilih.framer.website) and for the sample in this study as many as 100 Respondents using the Simple Random Sampling Technique. The Data Collection Technique from this study used a Closed Questionnaire with Likert Scale Statements distributed via Google Form through Distribution using Social Media Instagram, X, Tiktok, and also Whatsapp Media to Respondents who met the Inclusive Criteria that had been determined. Furthermore, the Correlation Technique used is Product Moment Correlation. The Results of the Research Hypothesis Test showed that based on the calculated r value (Pearson Correlation), the calculated r value was 0.559 > r table 0.361. So, it can be concluded that there is a relationship or Correlation between the BijakDemokrasi.Id Website Variable (bijakmemilih.framer.website) and the Young Generation Political Literacy Improvement Variable and the relationship between the Two Variables is Positive.